2006
DOI: 10.1152/jn.00423.2006
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Gating of Sensory Inputs by Zona Incerta

Abstract: We have previously shown that the GABAergic nucleus zona incerta (ZI) suppresses vibrissae-evoked responses in the posterior medial (POm) thalamus of the rodent somatosensory system. We proposed that this inhibitory incerto-thalamic pathway regulates POm responses during different behavioral states. Here we tested the hypothesis that the cholinergic reticular activating system, implicated in regulating states of arousal, modulates ZI activity. We show that stimulation of brain stem cholinergic nuclei (laterodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 27 publications
8
89
0
Order By: Relevance
“…We obtained single-unit, electrophysiological recordings from urethane-anesthetized rats, as previously described [24,50,61]. Consistent with our previous findings after electrolytic lesions of the spinothalamic tract [13], SCI significantly increased both spontaneous and sensory-evoked responses of PO neurons, as evidenced by comparing peri-stimulus time histograms (Fig.…”
Section: Administration Of Cdk Inhibitor Cr8 Reduces Sci-induced Hypesupporting
confidence: 81%
See 1 more Smart Citation
“…We obtained single-unit, electrophysiological recordings from urethane-anesthetized rats, as previously described [24,50,61]. Consistent with our previous findings after electrolytic lesions of the spinothalamic tract [13], SCI significantly increased both spontaneous and sensory-evoked responses of PO neurons, as evidenced by comparing peri-stimulus time histograms (Fig.…”
Section: Administration Of Cdk Inhibitor Cr8 Reduces Sci-induced Hypesupporting
confidence: 81%
“…At least 45 days after SCI, rats were anesthetized with urethane and prepared for extracellular recordings as previously described [24,50]. We selected urethane because it has no, or negligible, effects on glutamatergic and gamma-aminobutryic acid (GABA)ergic transmission, and therefore produces only minimal disruption of signal transmission [51].…”
Section: Extracellular Recordingsmentioning
confidence: 99%
“…In vitro, carbachol presynaptically suppressed GABAergic inputs to POm neurons. We recently demonstrated that the cholinoceptive, GABAergic inputs to POm arise from the zona incerta (see following text; Trageser et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that both spontaneous and vibrissae-evoked activity of ZI neurons are suppressed by cholinergic inputs from the brain stem reticular activating system (Trageser et al 2006). Because these cholinergic inputs are responsible for transitions between behavioral states, such as sleep and alertness (Steriade 2003), we suggested a statedependent gating hypothesis, where differing behavioral states-regulated by the brain stem cholinergic system-modulate ZI activity, thereby modulating the response properties of POm neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation